A review of the child care centre act 1984 in ensuring the safety and welfare of the children at a child care centre / Noor Zakilah Mohamad Isa and Rosmawati Haron - Mohamad Isa, Noor Zakilah; Haron, Rosmawati (2012)
The study attempts to identify the registration process and regulations and barriers in implementing the provided law in Malaysia. Data were gathered from literature review and interviews of the authorities and the Child Care Centre providers. The report shall look at the implication of licensing, enforcement and training module to the safety and welfare of a child at the child care centre. The objectives of the report namely i) to analyze the effectiveness of the registration process under the Childcare Centre (Amendment 2007) Act. ii) To point 'out the weaknesses, loopholes and area of improvement in the system either on the authorities, the law itself or the childcare providers.iii) To examine the practicability of the laws provided with special references to the terms and conditions imposed as regards to the licensing and the approval of the Childcare Centre with special focus on its registration, the premise and the childcare provider. The report concluded that system, enforcements and monitoring are main contribution of problems in registration process of Child Care Centre in Malaysia therefore specific research and study to review on the safety and welfare of the child care centre should be further carried on so that policies on the child care centre and development, the provision of child care centre services and the licensing procedure will be based on the true facts and legal compliance. It can conclude that the initial problem of child care centre in Malaysia is start from licensing. If the licensing procedure could be manage according to the law, the enforcement issues and other child care issues can be cured concurrently. The licensing is the basic compliance that can curb, monitor, enforce and settle the non-compliance.